2017
DOI: 10.5937/ratpov54-14254
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Trichoderma spp. against Common Fungal Pathogens

Abstract: Summary: Nowadays, organic food production demands more environmental friendly control of plant diseases. Biocontrol based on Trichoderma spp. usage is a promising due to Trichoderma is aggressive to broad range of phytopathogenic fungi. Given that, the aim of this study was to test in vitro antagonistic ability of ten native Serbian Trichoderma strains to ten common fungal pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…to control pathogenic fungi belonging to the genus Sclerotinia has been reported in various plants. Tancic-Zivanov et al (2016) and Tozlu et al (2016) found that (Td22) fungal antagonists effectively control S. sclerotiorum in lettuce plantations. A similar result was also reported by Colak-Ates ( 2019), who found that T. harzianum protects lettuce plants from attack by Sclerotinia sclerotiorum with percentage protection of between 80 and 86%, when applied in the field in combination with Coniothyrium minitans at the rate of 4 kg/ha.…”
Section: Resultsmentioning
confidence: 99%
“…to control pathogenic fungi belonging to the genus Sclerotinia has been reported in various plants. Tancic-Zivanov et al (2016) and Tozlu et al (2016) found that (Td22) fungal antagonists effectively control S. sclerotiorum in lettuce plantations. A similar result was also reported by Colak-Ates ( 2019), who found that T. harzianum protects lettuce plants from attack by Sclerotinia sclerotiorum with percentage protection of between 80 and 86%, when applied in the field in combination with Coniothyrium minitans at the rate of 4 kg/ha.…”
Section: Resultsmentioning
confidence: 99%
“…Estudos in vitro com outros fitopatógenos como Fusarium spp., Ascochyta spp., Pyrenophora teres e Sclerotinia sclerotiorum, utilizando Trichoderma sp. como biocontrolador, mostraram Trichoderma como um antagonista eficiente, inibindo o crescimento micelial dos fitopatógenos em mais de 50% (TANCIC-ZIVANOV et al, 2017). Esses testes in vitro são importantes no processo de seleção de isolados para o biocontrole, pois fornecem informações em condições controladas sobre a eficiência e a variabilidade dos isolados quanto à capacidade de colonização das estruturas do patógeno e o potencial de hiperparasitismo e competição por espaço e nutrientes, bem como a suscetibilidade de patógenos aos respectivos agentes (NASCIMENTO et al, 2016).…”
Section: Resultsunclassified
“…Net blotch is widely distributed and is one of the economically most significant diseases in all regions of the world where barley (H. vulgare) is commercially cultivated (Williams et al 2001;Frisen et al 2006;Tuohy et al 2006;Liu et al 2012;Adawy et al 2013;Novakazi et al 2019;Backes et al 2021). The disease is present in many European countries, including Serbia (Tančić-Živanov et al 2017) and other countries that previously formed Yugoslavia such as Bosnia and Herzegovina (Stojčić & Trkulja 2001; Tomić unpublished data), Russia (Afanasenko et al 2007;Mikhailova et al 2010;Volkova et al 2020), Italy (Aragona et al 2000;Rau et al 2003), France (Arabi et al 1992;Youcef-Benkada et al 1994;Toubia-Rahme et al 1995), Hungary (Tóth et al 2008), Poland (Baturo-Ciesniewska et al 2012, Finland (Peltonen et al 1996;Robinson & Jalli 1996;Serenius et al 2005;Tuohy et al 2006), Slovakia (Tuohy et al 2006), Ukraine (Retman et al 2022), Lithuania (Statkeviciute et al 2010(Statkeviciute et al , 2012, Estonia (Sooväli & Koppel 2010), Norway (Tuohy et al 2006;Wonneberger et al 2017), Sweden (Jonsson et al 1997;Tuohy et al 2006), Denmark (Smedegård-Petersen 1971Tuohy et al 2006), Germany (Vatter et al 2017), Czech Republic…”
Section: Geographical Distributionmentioning
confidence: 99%